Systematic review of live surgical demonstrations and their effectiveness on training. Issue 13 (13th October 2014) - Brunckhorst, O.; Challacombe, B.; Abboudi, H.; Khan, M. S.; Dasgupta, P.; Ahmed, K.
<x xml:space="preserve">Abstract</x> Background Live surgical demonstrations are commonly performed for surgical conferences. These live procedures have recently come under scrutiny, in particular with issues pertaining to patient safety. This systematic review aimed to explore the evidence for live surgery as a training tool, and to investigate the safety of live surgical broadcasts. Methods PubMed, Embase, MEDLINE and Cochrane Library databases were searched using a predefined search strategy from January 1980 to October 2013. Specialty Societies and primary Colleges of Surgeons were searched for guidelines or position statements on live surgical teaching. Results Educational value criteria demonstrated for live surgery included feasibility, acceptability, construct and concurrent validity. Complication rates during live procedures were not compromised in the majority of studies. Patient safety, however, may be affected during live procedures as success rates have been found to be lower in some studies. Only Cardiothoracic, Urology and Vascular Surgical Societies currently offer guidelines on conducting live surgical demonstrations. Conclusion Little evidence exists on the safety and educational value of live surgery, with few studies of high quality conducted. Guidance on live procedures is scarce, with only three major surgical specialties offering any advice. More needs to be done to establish and promote evidence for the value of live surgery demonstrations.